Rural Technology Development and Delivery RuTAG and Its Synergy with Other Initiatives - Saha, Subir Kumar; Ravi, M. R.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book comprises the proceedings of a rural technologies conference organised by the Rural Technology Action Group (RuTAG), which was conceptualized and initiated by Principal Scientific Adviser (PSA) to the Government of India R. Chidambaram in 2003-04. The book highlights case studies and research into providing science and technology interventions for the development of rural areas. Covering various aspects of research carried out in the area of rural technologies, it offers a valuable resource for researchers, professionals, and policymakers alike.
Summary of Keynote Lectures and Panel Discussions of RTDD-2018 -- Improved Technologies Under the Rural Technology Action Group (RuTAG) at IIT Delhi -- Technology Interventions for Rural Development by RuTAG IIT Bombay: A Review -- Review of Science and Technology Interventions developed by Rural Technology Action Group- Tamil Nadu, IIT Madras -- A Comprehensive Review on Projects carried out by RuTAG Centre IIT Roorkee -- Design and Development of Technology Appropriate for Rural Community to Address Sustainability -- Understanding Barriers to Adoption of Grass-root Innovations - A Case Study of RuTAG Technologies -- Development of a Solar-powered Treadle Pump -- Failure Analysis of Comb for Sheep Hair Shearing Device -- High-frame-rate Video Analysis for Mobile Vibration-based Crop Inspection -- Tribology of steel-steel contact: Comb-cutter assembly for Sheep hair shearing device developed at IIT Delhi -- Redesigning the humble NMC (New model charkha) -- Improving the Design of Bullock Driven Tractor (BDT) to Make it User-Friendly -- Developments to Overcome Problems in Traditional Process of Making Glass Bangles -- Technologies to support the technologies -- Development of a Low-Cost Ground Water Level Measuring Device -- Evolution of 'Floating fish cages for inland waters' developed by RuTAG IIT Bombay -- Study of supply chain, production potential of hirda and design of hirda decortication machine for livelihood generation for tribal people -- Street Food Cart Design: a critical component of Food Safety -- Design of a Low-Cost Full-Face Mask for Stone Carvers -- Chirala Handloom Cluster - A solution to convert the tedious job of street sizing into a more of efficient/ergonomic/easier process -- Development of Modified Pump Used as Turbine in Micro Hydro Plants -- A Cost Effective and Field Deployable System for Soil Macronutrient Analysis Based on Near-infrared Reflectance Spectroscopy.-Designing a cow lift for downer cow: Experience of working on a rural technology -- Design and Development of Mechanical and Electronic Jacquard Handloom for Fine-Korai-Mat Weaving -- Development of Modified Bageshwari Wool Charkha.
Keywords: Engineering design; Sustainability; Technological innovations; Engineering Design; Sustainability; Innovation and Technology Management